The Educational Game Guess the Picture of Balanced Nutrition in Groups of Elementary School Children: Health Education - Fransiska Novita Sari; Maria Floriana Ping; Muh. Taufiqurrahman (CV. Media Digital Publikasi Indonesia, 2023)
The group of elementary school age children is a stage of life where children experience rapid growth and development. Imbalance between nutritional intake and daily needs can cause nutritional health problems. This community service activity was carried out as an effort to promote health in groups of elementary school age children. Balanced nutrition education using picture guessing game media. Participants in this community service were 70 students from grades 1-6 in one of the elementary schools in Sungai Bawang Village, Kutai Kartanegara Regency. The final results of this activity show an increase in the mean value of knowledge from 5.96 to 6.23 and the p value (0.000). Health education using games can increase children's interest in learning about efforts to maintain health